782.
3) x = 4
5) y = 6
783
1) x = 3
2) x = 7
Пошаговое объяснение:
3)
x - 2/3 = 5/6x (Умножаем на 6)
6x - 4 = 5x
x = 4
5)
2/3y - 1/3 = 5/9y (Умножаем на 9)
6y - 6 = 5y
y = 6
783.
1)
7x - (3 + 2x) = x + 9
7x - 3 -2x = x + 9
7x - 2x - x = 9 + 3
4x = 12
x = 3
2)
13 - (2x - 5) = x - 3
13 - 2x + 5 = x - 3
-2x - x = -3 - 5 - 13
-3x = -21
x = 7
782.
3) x = 4
5) y = 6
783
1) x = 3
2) x = 7
Пошаговое объяснение:
782.
3)
x - 2/3 = 5/6x (Умножаем на 6)
6x - 4 = 5x
x = 4
5)
2/3y - 1/3 = 5/9y (Умножаем на 9)
6y - 6 = 5y
y = 6
783.
1)
7x - (3 + 2x) = x + 9
7x - 3 -2x = x + 9
7x - 2x - x = 9 + 3
4x = 12
x = 3
2)
13 - (2x - 5) = x - 3
13 - 2x + 5 = x - 3
-2x - x = -3 - 5 - 13
-3x = -21
x = 7